Quantification of optic disc edema during exposure to high altitude shows no correlation to acute mountain sickness - Willmann, Gabriel; Fischer, M. Dominik; Schatz, Andreas; Schommer, Kai; Messias, Andre; Zrenner, Eberhart; Bartz-Schmidt, Karl U.; Gekeler, Florian (PLOS ONE, 2011)
Background The study aimed to quantify changes of the optic nerve head (ONH) during exposure to high altitude and to assess a correlation with acute mountain sickness (AMS). This work is related to the Tuebingen High Altitude Ophthalmology (THAO) study. Methodology/Principal Findings A confocal scanning laser ophthalmoscope (cSLO, Heidelberg Retina Tomograph, HRT3®) was used to quantify changes at the ONH in 18 healthy participants before, during and after rapid ascent to high altitude (4559 m). Slitlamp biomicroscopy was used for clinical optic disc evaluation; AMS was assessed with Lake Louise (LL) and AMS-cerebral (AMS-c) scores; oxygen saturation (SpO2) and heart rate (HR) were monitored. These parameters were used to correlate with changes at the ONH. After the first night spent at high altitude, incidence of AMS was 55% and presence of clinical optic disc edema (ODE) 79%. Key stereometric parameters of the HRT3® used to describe ODE (mean retinal nerve fiber layer [RNFL] thickness, RNFL cross sectional area, optic disc rim volume and maximum contour elevation) changed significantly at high altitude compared to baseline (p<0.05) and were consistent with clinically described ODE. All changes were reversible in all participants after descent. There was no significant correlation between parameters of ODE and AMS, SpO2 or HR. Conclusions/Significance Exposure to high altitude leads to reversible ODE in the majority of healthy subjects. However, these changes did not correlate with AMS or basic physiologic parameters such as SpO2 and HR. For the first time, a quantitative approach has been used to assess these changes during acute, non-acclimatized high altitude exposure. In conclusion, ODE presents a reaction of the body to high altitude exposure unrelated to AMS.
Gesehen am 03.11.2022